Investigation of subbituminous coal and lignite combustion processes in terms of mercury and arsenic removal. (1st September 2019) - Marczak, M.; Wierońska, F.; Burmistrz, P.; Strugała, A.; Kogut, K.; Lech, S.
Abstract: The aim of this work was to determine the Hg and As behaviour during coal combustion and flue gas purification process in terms of reducing their emissions into the atmosphere. The distribution of Hg and As between the solid phase (ash) and the gaseous phase was determined. Due to the high volatility, almost all of the mercury introduced into the installation passed to the flue gas. In the case of the As, more than 70% of the As passed to the flue gas, while the rest was recorded in the ashes. Three dusty sorbents were examined in terms of the effectiveness of flue gas purification from Hg and As: powdered activated carbon PAC, coke dust, and filter cake. The average efficiency of mercury removal for subbituminous coal and lignite ranged from 85 to 93% and 61 to 80%, respectively. On the other hand, the efficiency of As removal for subbituminous coal ranged from 21.8% to 90.8% depending on the sorbent used. The research was carried out in a laboratory scale tube furnace. The coal sample was burned in the flow of air and flue gas was directed through the sorbent container or scrubbers. The analysis was performed in defined and controlled conditions which included: combustion temperature, time, temperature of flue gas passing through the sorbent and flow rate.